The Effectiveness of Student Gymnastics in 2022 on Improving Physical Fitness: - Noviria Sukmawati; Selvi Melianty; Selvi Atesya Kesumawati; Fanni Nur Rahma (UNIB Press, 2023)
Physical fitness can be obtained through proper, systematic, and not excessive physical exercise. One of the sports activities in supporting physical fitness is the SKJ Student 2022 exercise. Physical fitness can be obtained through proper, systematic, and not excessive physical exercise. One of the sports activities in supporting physical fitness is the SKJ Student 2022 exercise. The purpose of this study was to determine Effectiveness of Student Gymnastics in 2022 on Improving Physical Fitness. This type of research uses experimental research. The population in this study were all students of the Sports Education Study Program at Bina Darma University Palembang, totaling 44 people. The instruments in this study were the Indonesian Physical Fitness Test (TKJI), namely; 1) 60 meter sprint, 2) 60 second elbow hanging test, 3) 60 second lying seat, 4) upright jump, and 5) 1000 meter run. The results showed that the 2022 student physical fitness exercise was effective in improving the physical fitness of students of the Bina Darma University Sports Education Study Program Palembang, with an average value before (pre-test) physical fitness exercise training was 12.89, while the average value after (post-test) student physical fitness exercise training 2022 was 16.02.